Market studies mapping, theorizing and impacting market action - Geiger, Susi; Mason, Katy; Pollock, Neil (Cambridge University Press, 2025)
Market studies is a newly emerging field dedicated to understanding the origins, core concepts, theories and methods currently being used and developed to examine markets in the making. Providing a unique overview that introduces, positions and develops this highly fertile area of research, Market Studies is the first book to consolidate its themes, tools and methods in a single, comprehensive volume. Topics covered include: market organization and design; performativity in and around markets; valuation; market places and spaces; methods that may be utilized in studying markets; the field's relation to adjacent disciplines; the future of markets. Deploying a sensitivity for the socio-material constitution of markets, the authors put market practices at the centre of inquiry and offer insights into the future and potential impact of market studies research. The contemporary, practical and interdisciplinary approach is strengthened by multiple examples of original empirical research into markets
Title from publisher's bibliographic system (viewed on 11 Nov 2024)
Keywords: Markets; Capitalism